Assessing cumulative watershed effects by zig-zag pebble count method - Nex Betin, Timothy (2006)
Cumulative effects are the combined effects of multiple activities for example such as agricultural activities, logging activities, unpaved roads, grazing and recreation, while the watershed effects are those which involve processes of water transport. Almost all impacts are influenced by multiple activities, so almost all impacts must be evaluated as cumulative impacts rather than as individual impacts. This paper attempts to present and discuss the cumulative effects occur within the Endau watershed, current issues on water resource planning and management and the approaches/strategies required to confront present and emerging critical problems. In this study, the deposition of fine sediment (particle size < 8 mm) are main concern because this can adversely affect macro-invertebrates and fish by filling pools and interstitial spaces, decreasing inter-gravel dissolved oxygen concentrations, and inhibiting fish fry emergence. The bed material particle-size distribution is believed to be one of the first channel characteristics to change in response to management activities. This study was carry out on Jasin River as reference stream while Mengkibol River and Sembrong River and as study stream. The method for assessing these CWEs is by using Zig-Zag pebble count method. As result, the sediment loading is in the order of Sembrong River > Mengkibol River > Jasin River. As the Sembrong River is heavily silted, sediment transport process is expected to be more active here compared to the Mengkibol River. For the Jasin River, due to the presence of much larger material, movement of fine particles is impeded thus minimizing sediment transport. From the study, it suggests that agricultural erosion is the primary sediment source due to the large areas involved and the land disturbance effects of cultivation. This follows up by urban erosion due to sediment originates mainly from exposed soils in areas under construction and from street dust and litter accumulation on impervious surfaces